Investigating the Growth of Nationalism Character in Indonesian Elementary School Students: A Case Study - Prihatmojo, Agung; Sartono, Emmanuel Kus Eddy; Wibawa, Lutfi; Ardiansyah, Amalia Rizki; Elmiati, Elmiati; Maharromiyati, Maharromiyati; Purwandari, Septiyati; Al Fuad, Zaki; Hartono, Deni Puji; Yarid, Hatta; et al. (Journal of Ethnic and Cultural Studies, 2026)
Nationalism character is vital in fostering national identity, patriotism, and civic responsibility among students. This study applied Latent Growth Modeling (LGM) to examine the development of students’ nationalism during a four-session educational intervention focused on promoting nationalism through classroom discussions, activities, and multimedia resources. Participants included 131 elementary school students from Yogyakarta, Indonesia. The study evaluated changes in students’ knowledge and attitudes toward nationalism, specifically targeting respect for national symbols, national heroes, and cultural diversity. Findings revealed a significant overall increase in nationalism character, with a mean growth rate of 20.305 (p < 0.001) on a 4-point Likert scale. The dimension of “Respecting National Symbols” showed the highest improvement (partial η² = 0.998), underscoring the intervention’s strong effect on emotional and cognitive engagement with national symbols. Variations in individual growth trajectories were also observed, highlighting the need for personalized learning approaches. This research extends the literature by applying LGM to nationalism education and suggests that adaptive, individualized instruction is essential for strengthening nationalism education in contemporary, multicultural learning environments.